"Enemy at the Gates": An Analysis on India's Experiences with the Taliban. (December 2020) - Ghosh, Sourish
India's long history of relations with Afghanistan dates back to the time of the Mauryans. It became even stronger after India's independence in 1947. Since 1947, India has always maintained the policy to support whosoever comes to power in Kabul, but in 1996, there was a shift from that policy as the Taliban, a radical Islamist group, captured power. Pakistan has always been paranoid about India–Afghanistan relations as it never wanted hostile neighbours on both sides of its borders. Its urge for a friendly government in Kabul got satiated when the Taliban came to power, with its support. New Delhi did not recognize the Taliban government and, instead, shunned all diplomatic relations with Kabul. It was only after the Taliban regime was ousted through the US intervention that India rejuvenated its relations with Kabul. However, even after 19 years of intervention, the Taliban remained a potent force, and now as the USA plans to withdraw from Afghanistan, it is trying to negotiate a peace settlement with the Taliban. Currently, India too is trying to engage in dialogues with the Taliban, which again marks a shift from its earlier strategy. This study analyzes India's experiences with the Taliban and shift in its policy from the pre-9/11 period (1996–2001) to the post-9/11 period (2001–early 2019).